The city modeled like ecosystem: principles and strategies for sustainability of the systems of urban metabolism city. (2015)
The concept of urban metabolism was first used by Wolman (1965) to quantify the flows of energy and materials in and out of a hypothetical city and was developed by Douglas (1983), which describes the equations to measure energy, water and balances that constitute the urban metabolism. However, most studies are focused on research rather than practice-oriented and tend to focus on one or more aspects of urban metabolism. The proper integration of available models has not yet managed to give an integral vision of urban sustainability in support of assessment practices of planning and impact (Zhang, 2013). The urban metabolism is built from systems such as water, energy and materials, and generally these systems have a linear sequence of processing, so that the operation of the city depends entirely on imported resources high quality. So in terms of the linear resource management is highly inefficient metabolism and promotes a high dependence on external resources to the city (Leduc & Van Kann, 2012). The analysis of urban metabolism can be an important tool for the study of urban ecosystem. Cities like artificial systems can be redesigned from a better perspective as ecosystems natural, but what approaches should be considered for simulating a natural ecosystem? For this it is appropriate to analyze the performance standards of the urban system based on ecological principles and methods. When a city is compared as a living organism studying its urban metabolism, all flows of energy and materials must be considered.